National BTS bronchiectasis audit 2012: is the quality standard being adhered to in adult secondary care?. Issue 3 (22nd July 2013) - Hill, Adam T; Routh, Chris; Welham, Sally
Abstract : A significant step towards improving care of patients with non-cystic fibrosis bronchiectasis was the creation of the British Thoracic Society (BTS) national guidelines and the quality standard. A BTS bronchiectasis audit was conducted between 1 October and 30 November 2012, in adult patients with bronchiectasis attending secondary care, against the BTS quality standard. Ninety-eight institutions took part, submitting a total of 3147 patient records. The audit highlighted the variable adoption of the quality standard. It will allow the host institutions to benchmark against UK figures and drive quality improvement programmes to promote the quality standard and improve patient care.